2017
DOI: 10.1177/2045125317743651
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine prescription in Ontario residents aged 65 and over: a population-based study from 1998 to 2013

Abstract: Background:Although commonly used in anxiety and insomnia, recent guidelines recommend caution when prescribing benzodiazepines in the elderly. Here we examined rates of benzodiazepine prescribing to older adults in Ontario, Canada from 1998 to 2013 and impact of legislation that made prescribing regulations more strict.Method:Annual benzodiazepine prescription rates for Ontario residents aged 65 and over were examined using the Ontario Drug Benefit database which captures all publicly funded prescriptions. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
5
22
1
Order By: Relevance
“…A recently published Swiss study using claims data found no association between use and the risk of Alzheimer’s disease,31 contrary to previous evidence 32. In other countries the prevalence of benzodiazepine use in the elderly population ranged from 15% to 31% 1 6 33–35. In our study, about 20% of enrollees received at least one benzodiazepine prescription in 2017, with two-thirds of them receiving the equivalent of 30 DDD or more, and 80% with estimated treatment durations longer than 2 weeks.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…A recently published Swiss study using claims data found no association between use and the risk of Alzheimer’s disease,31 contrary to previous evidence 32. In other countries the prevalence of benzodiazepine use in the elderly population ranged from 15% to 31% 1 6 33–35. In our study, about 20% of enrollees received at least one benzodiazepine prescription in 2017, with two-thirds of them receiving the equivalent of 30 DDD or more, and 80% with estimated treatment durations longer than 2 weeks.…”
Section: Discussioncontrasting
confidence: 96%
“…Moreover, healthcare providers may not recommend discontinuing benzodiazepines due to concerns related with withdrawal symptoms, which may occur in up to 50% of patients 38. Our findings are consistent with previous research33 39 40 showing higher prevalence of prescription among women. The increase of benzodiazepine prescription with the number of chronic conditions can be partly explained by poorer quality of sleep and more prevalent anxiety in this group.…”
Section: Discussionsupporting
confidence: 89%
“…The high prevalence of benzodiazepine use in this French cohort is a striking finding of this study: benzodiazepines appear to be used much more frequently in these older patients with schizophrenia than in general populations or even in older adults receiving residential care (Brimelow et al, 2018). In our own jurisdiction of Ontario, Canada, 14.8% of the 2.1 million residents aged over 65 were prescribed a benzodiazepine in the year 2013 (Davies et al, 2018). The figure in the French cohort is not only more than twice that reported in the Ontario population aged over 65, but also is based on the much stricter criteria of benzodiazepines being prescribed at one specific time (point prevalence), as opposed to the lower threshold in our populationbased data that required only one prescription in the calendar year.…”
mentioning
confidence: 62%
“…41 This trend toward a decline in benzodiazepine use might indicate a change in prescribing culture supported by local policies in these countries. 40,41 Similarly, the reduction in BZRA use in Belgium might be the result of several national campaigns targeting physicians, pharmacists, and patients to S3. b 2 missing values (n = 2/1286; 0.2%).…”
Section: Factors Associated With Bzra Use In 2013mentioning
confidence: 99%